The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00063-013-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of outcome scores in patients suffering from cardiogenic shock complicating AMI

Abstract: Acute myocardial infarction (AMI) is complicated by cardiogenic shock (CS) in 7-10% of cases and the mortality rate is about 60-70% [13,16]. Early revascula rization by percutaneous coronary inter vention (PCI) and intensive care includ ing positive inotropic agents, vasopres sors, and circulatory assist devices are routinely used to improve cardiac output and to prevent multiorgan failure [1,5,16]. Intraaortic balloon pump (IABP) is a commonly used mechanical support sys tem for patients with CS [25,33]. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…It derives from increased lactate production in hypoperfusion states or decreased lactate clearance that may also be secondary to liver dysfunction. Indeed, multiorgan damage and failure, or systemic pathways activated in the state of cardiogenic shock, have been suggested to contribute to the detrimental prognosis …”
Section: Discussionmentioning
confidence: 99%
“…It derives from increased lactate production in hypoperfusion states or decreased lactate clearance that may also be secondary to liver dysfunction. Indeed, multiorgan damage and failure, or systemic pathways activated in the state of cardiogenic shock, have been suggested to contribute to the detrimental prognosis …”
Section: Discussionmentioning
confidence: 99%
“…Early outcomes may be improved by optimizing hemodynamics and perfusion with MCS and vasoactive agents. However, once there is a systemic inflammatory state and multisystem organ failure, even full mechanical support and normalization of cardiac output may not improve survival, which is no longer mediated by hypoperfusion alone (19,20). Further studies are therefore needed to address several questions, including the ideal timing of MCS, the role of TCS, and identification of patients who do not derive benefits from MCS.…”
Section: Discussionmentioning
confidence: 99%
“…Risk scores have gained increasing importance for decision making in critically ill patients. Currently, the APACHE II and the SAPS II scores are the most useful ICU assessment tools for the prognostic outcome of critically ill patients (Knaus et al, 1985;LeGall et al, 1984), but for CS patients these scores are less useful, since a recent study reported sensitivity and specificity rates below 80% in a contemporary CS cohort (Kellner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, currently available ICU outcome scores appear to be inappropriate to guide the management of CS patients (Kellner et al 2013).…”
Section: Introductionmentioning
confidence: 99%